Pharmacokinetic and pharmacodynamic analysis of enteric‐coated mycophenolate sodium: limited sampling strategies and clinical outcome in renal transplant patients - Sommerer, Claudia; Müller‐Krebs, Sandra; Schaier, Matthias; Glander, Petra; Budde, Klemens; Schwenger, Vedat; Mikus, Gerd; Zeier, Martin (British journal of clinical pharmacology, 2010)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Therapeutic drug monitoring of mycophenolate mofetil is a promising tool for reducing acute rejection episodes after renal transplantation. • Limited sampling algorithms of mycophenolic acid in mycophenolate mofetil‐treated renal transplant patients have been established. • Recently published study results indicate that the intensity of early drug exposure might determine the risk of acute rejection episodes. WHAT THIS STUDY ADDS • This study provides pharmacokinetic and pharmacodynamic data of mycophenolic acid in enteric‐coated mycophenolate sodium‐treated renal transplant patients. • Limited sampling algorithms are evaluated and a practical sampling strategy with five sampling time points within the first 4 h after oral drug intake is provided in renal transplant patients with combined immunosuppression consisting of enteric‐coated mycophenolate sodium and ciclosporin A. • The association between pharmacokinetic and pharmacodynamic parameters and the risk of adverse events are evaluated. • Both pharmacokinetic and pharmacodynamic parameters contribute to optimized individual immunosuppression. AIMS Pharmacokinetic (PK) and pharmacodynamic (PD) monitoring strategies and clinical outcome were evaluated in enteric‐coated mycophenolate sodium (EC‐MPS)‐treated renal allograft recipients. METHODS PK [mycophenolic acid (MPA)] and PD [inosine monophosphate dehydrogenase (IMPDH) activity] data were analysed in 66 EC‐MPS and ciclosporin A (CsA)‐treated renal allograft recipients. Adverse events were considered in a follow‐up period of 12 weeks. RESULTS Analyses confirmed a limited sampling strategy (LSS) consisting of PK and PD data at predose, 1, 2, 3 and 4 h after oral intake as an appropriate sampling method (MPA r2= 0.812; IMPDH r2= 0.833). MPA AUC0–12 of patients with early biopsy‐proven acute rejection was significantly lower compared with patients without a rejection (median MPA AUC0–12 28 µg*h ml−1 (7–45) vs. 40 µg*h ml−1 (16–130), P < 0.01), MPA AUC0–12 of patients with recurrent infections was significantly higher compared with patients without infections (median MPA AUC0–12 65 µg*h ml−1 (range 37–130) vs. 37 µg*h ml−1 (range 7–120), P < 0.005). Low 12‐h IMPDH enzyme activity curve (AEC0–12) was associated with an increased frequency of gastrointestinal side‐effects (median IMPDH AEC0–12 43 nmol*h mg−1 protein h−1[range 12–67) vs. 75 nmol*h mg−1 protein h−1 (range 15–371), P < 0.01]. CONCLUSIONS Despite highly variable absorption data, an appropriate LSS might be estimated by MPA AUC0–4 and IMPDH AEC0–4 in renal transplant patients treated with EC‐MPS and CsA. Regarding adverse events, the suggested MPA‐target AUC0–12 from 30 to 60 µg*h ml−1 seems to be appropriate in renal allograft recipients.